Analysis of Legal Protection for Women Victims of Rape - naziah, firqotun (Universitas Negeri Semarang, 2017)
Human rights are a set of rights that are inherent in the nature and existence of humans as creatures of God Almighty and are His gifts that must be respected, upheld and protected by the state, law, government and everyone, for the honor and protection of human dignity. . Women are vulnerable to becoming victims of crime because of their weak position. Crimes that are often experienced by women are immoral crimes. One of the immoral crimes that often victimize women is rape. The crime of rape is a form of violence against women which is an example of the vulnerability of women's position, especially towards men's sexual interests. The sexual image of women which has been placed as a male sexual object, in fact has far-reaching implications for a woman's life, so that she is forced to always face violence, coercion and torture physically and psychologically. Rape seriously violates human rights because in rape cases many of the rights of the victim are taken away by the perpetrator. One of the cases that occurred was a student with the initials EW who was the victim of the rape of five men. Many human rights were violated by the perpetrators, including: women's rights, the right to feel safe, the right to safe asylum, the right to protection, etc. Victims of rape need protection from the law so that the crime of rape does not happen again and help victims to deal with the psychological and mental impacts they experience by way of victim restusation and medical assistance and psycho-social assistance.